Üstel Fonksiyon İçin Yeni Bir Yaklaşım Kullanarak Cmos Kazancı Ayarlanabilir Kuvvetlendirici Tasarımı - Altuner, Muhammet Sait (Fen Bilimleri Enstitüsü, 2015)
Kazancı ayarlanabilir kuvvetlendiriciler, geniş dinamik aralık gerektiren uygulamalar açısından vazgeçilmez bir unsurdur. Kontrol işlemi, geniş dinamik aralık söz konusu olduğunda üstel fonksiyonların kullanımını zorunlu kılar. Bu sebeple günümüzde bu yapıların tasarımında üstel fonksiyonların kullanımı ön plana çıkmaktadır. Fakat modern teknolojilerde geniş dinamik aralığı ihtiyacıyla birlikte yüksek frekans, düşük güç tüketimi, düşük gürültü, küçük kırmık alanı gibi ihtiyaçlar da söz konusu olduğu için tasarım yöntemleri, kullanılan teknolojiler ve kullanılan bloklar farklılaşmaktadır. Bu çalışmada, 0.18mm CMOS teknolojisi kullanılarak bir kazancı ayarlanabilir kuvvetlendirici tasarlanmıştır. Elektronik sistemlerde işaretlerin algılanması veya işlenmesi için gerekli ihtiyaçlardan biri de işaretin bloklar arası geçişi sırasında uyumluluk sağlanmasıdır. Kabaca işaret uyumlaması ihtiyacı iki genel durumda ortaya çıkar; bunlardan ilki, tasarımcının bir giriş işareti seviyesini uygulanacak elemanın giriş aralığına uyumlamasını gerektiren durumlardır, ikincisi ise, tasarımcının çeşitli kayıpların yerini doldurmak için giriş değerini sabitleme ihtiyacı olduğu durumlardır. Kazancı ayarlanabilir kuvvetlendiriciler bu ihtiyaca yönelik tasarlanmış devrelerin temelini oluşturan yapılardır. Genel anlamıyla, kazanç değerini elektronik olarak ayarlayarak işaret uyumlaması yapan kuvvetlendiricilerdir. Kazanç değerini ayarlama işlemi için kullanılan yöntemler; geniş kontrol aralığı, geniş frekans aralığı, yüksek doğruluk, yüksek hız gibi uygulama alanına yönelik ihtiyaçlara göre farklılık göstermektedir. Kazancı kontrol eden yapıların temelleri Gilbert tarafından 1968 yılında yapılmıştır. Daha sonra, "ayarlanabilir kazanç kontrol hücresi" adlı bu devreler Willy Sansen tarafından geliştirilerek bugünkü topolojilerin ilk örnekleri gerçeklenmiştir. Bu çalışmalar akım yönlendirme yöntemi kullanılarak bipolar transistörlerle tasarlanan kuvvetlendirici yapılarıyla oluşturulmuştur. 80'li yıllarda BiCMOS teknolojisi, 90'lı yıllarda da CMOS teknolojisi ile kazancı ayarlanabilir kuvvetlendirici örnekleri ortaya çıkmıştır. CMOS teknolojisinin kullanımıyla birlikte matematiksel gerekliliklerden dolayı yeni kontrol yöntemleri önerilmeye başlanmıştır. Dolayısıyla kazancın üstel fonksiyon yaklaşıklıklarıyla kontrol edilmesi yöntemi de bu dönemlere denk gelmektedir. Öte yandan günümüzde en çok tercih edilen yöntemlerden olan sözde üstel fonksiyon yaklaşımının ilk örnekleri 1995 yılında Harjani tarafından önerilmiştir. Bu çalışmada, kazancı ayarlanabilir kuvvetlendiricilerin çalışmasının anlaşılması için literatürdeki kazanç ayarlama yöntemleri incelenip, sınıflandırması yapıldıktan sonra bu yöntemlerden biri olan sözde üstel fonksiyon yaklaşımı yöntemi için geniş frekans aralığı ihtiyacı gözetilerek yeni bir üstel yaklaşım önerilmiştir. Gerçeklemek üzere kazancı ayarlanabilir kuvvetlendirici yapısı tasarlanarak, gerekli analizler yapılmıştır.

Variable gain amplifiers are an essential part for applications which need wide dynamic range. When it comes to wide dynamic range, usage of exponential functions in control operation is a must. For this reason, instead of other methods exponential functions must be used in the design of these kind of structures. Even though the need of wide dynamic range is essential, need of high frequency, low power dissipation, low noise, small chip area differentiate the design technology and structure. In this work, a variable gain amplifier designed in 0.18mm CMOS technology. One of the needs for signal processing in electronic systems is to provide compatibility between the blocks. Briefly, need for signal matching appears in two general condition. First condition is when designer needs to match input signal range to the input range of device that is applied. Second condition is when designer needs to fix the input range from some losses such as noise, etc... Variable gain amplifiers are essential for circuits to answer these needs. Generally, a variable gain amplifier is a signal matching amplifier that electronically sets the gain value. Methods to set gain value differ on application specific conditions like wide dynamic range, wide band, high precision, high speed. Variable gain amplifier is an indispensable building block to maximize the dynamic range of modern wireless communication systems, as well as medical equipment, hearing aids, disk drives, and so on. A VGA is typically employed in a feedback loop to realize automatic gain control. There are two different techniques for VGA building. One employs a number of gain stages and the gain is discrete and digitally controlled. Therefore, this type of variable gain amplifier can be called programmable gain amplifier. The other employs a continuous amplifier and an analog gain control signal. Analog gain control is generally preferred because discrete gain control may cause some problems such as phase discontinuity. Various technologies, such as bipolar technology, BiCMOS technology and CMOS technology, can be used for the variable gain amplifier realization. However, the low cost and easy integration with the other parts of an integrated circuit have caused CMOS variable gain amplifiers to be preferred over other technologies. The gain of a variable gain amplifier is generally required to be an exponential function of a control signal. The exponential gain control is required to achieve a wide dynamic range and to maintain the AGC loop settling time independent of the input signal level. The exponential gain control can be easily obtained in bipolar transistor technology by means of the inherent exponential characteristics. However, it is difficult to realize this exponential function due to its inherent square or linear characteristics in CMOS technology. Although a transistor operating in a subthreshold region has an exponential characteristic, it is generally not preferred due to noise and small bandwidth. Another possible method is to use parasitic bipolar transistors to generate the exponential function. The linear-in-decibel gain control signal is generated using the relationship between a collector current and base-to-emitter voltage . This is strongly dependent on the temperature and process parameters. As a result, CMOS technologies do not give exponential characteristics except in weak inversion region. However the weak inversion is suitable only for low-frequency applications. To realize the exponential function in strong inversion region several approaches have been presented in the literature. In recent CMOS-based VGA designs, dB-linear gain variation characteristics are realized by the circuit implementations of rational expressions, pseudo exponential and Taylor series approximation functions. In order to realize wide decibel-linear range, high order approximation must be adopted. Another important aspect of a wide band variable gain amplifier is a large bandwidth. There are many systems for high-speed data communications such as ultra-wide band systems, wireless local area networks, and Bluetooth. These systems provide a high data rate with relatively low power consumption in short-range wireless communications. For high-speed data communication, the bandwidth of a variable gain amplifier must be very wide. Therefore, a wide band VGA is a key component. This study can be investigated in two parts. First part is research part which forms a basis for the new method. In the research part, the exponentially controlled variable gain amplifiers are investigated. Basic structures and basic blocks used in these structures are studied first. The basics of gain controlling structures are developed by Barrie Gilbert in 1968. Then methods are investigated. These are designs in Bipolar technology, in CMOS technology using weak inversion, designs which use Taylor approximation and designs which use Pseudo Exponential methods respectively. First, variable gain amplifiers which use Bipolar technology examined. Second variable gain amplifiers designed to work in weak inversion region are examined. After that the early designs in strong inversion region, which use Taylor series approximations are examined. And last, the important part of the study which is most used design technique nowadays in CMOS technology, Pseudo exponential function and its improved versions are researched. Pseudo exponential function, first proposed in 1995 by Harjani. After that various functions based on Harjani's function are proposed. In this paper, a new pseudo-exponential function is described which is an improved form of pseudo exponential function. After that a new CMOS exponential-control variable gain amplifier based on the new function is introduced. The new variable gain amplifier improved with a slight change. And these two circuits are designed, their layouts are generated and simulated. No multiplier is needed in the proposed approach. The variable gain amplifier operates in current mode and includes two different stages. The first stage is a simple current amplifier while the second stage is an attenuator. The overall behaviour of the stages gives the new pseudo-exponential function. The variable gain amplifier circuit has been designed and simulated for a 0:18mm CMOS process.
Design Of Cmos Variable Gain Amplifier Using A New Exponential Function Approximation
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Kazancı Ayarlanabilir Kuvvetlendirici; Analog Tümdevre Tasarımı; Variable Gain Amplifier; Analog Integrated Circuit Design